Aeronautical Meteorology in Aeronautical Language and in Aviation Language: a hybrid field? - Peixoto, Rafaela Araújo Jordão Rigaud; Pimentel, Janine Maria Mendonça (The ESPecialist, 2020)
Although Aeronautical Meteorology language is not generally regarded as standard communication between air traffic controllers and pilots, it plays an important role in Air Traffic Control (ATC) communication since it comprises phraseology and plain language used to communicate weather phenomena which interfere in aviation operations. Then, this paper focuses on the meteorology terminology used by Brazilian experts and discusses whether Aeronautical Meteorology is a hybrid field. Based on the theory of lexical semantics for terminology proposed by L’Homme (2020), the syntactic and semantic properties of a small set of Portuguese terms were analyzed in two separate textual corpora, i.e. a corpus representative of Aviation language and a corpus representative of Aeronautical language. For that, the combinatorics of terms were examined by means of a concordancing tool and were categorized by means of semantic labels. Quantification and comparison of the results obtained seem to suggest that the behavior of the terms in the two corpora share a fair amount of similarities.